A flipped classroom in law teaching - Anjos, Maria do Rosário (2019)
Globalization has introduced changes in communication between people, also affecting education in general. The intensification of the free circulation of people had generated a rethink of Higher Education. The Bologna Declaration operated a veritable "Copernican Revolution" advocating a European Higher Education Area and consequently the implementation of new teaching methodologies. In the teaching of the law there is a total absence of didactic and pedagogical training. The teaching indifference contributes to the lack of interest of students, with a negative impact on the acquisition of professional skills. We intend that this study constitutes one hand, a provocation, and the other, a critical reflection on the teaching of law in Portugal. As a result of our experience as Teachers of Higher Education in the area of Law, we implemented the flipped classroom methodology. The classroom becomes the place for teacher-student interaction, encouraging the latter to take a more active stance, collaborating in the construction of his knowledge. The results show great commitment of the student regarding this learning teaching method.